45 minutes within the four walls of a classroom: Problems and concerns of student teachers during their practicum - Szymańska-Tworek, Aleksandra; Turzańska, Agnieszka (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
Student practicum is an important part of teacher preparatory program. It is speculated that pre-service teachers who manage to complete their practicum with a sense of accomplishment and success are more likely to choose teaching as their ultimate career. However, before trainee teachers turn into fully-fledged, certified teachers, they need to work through the numerous challenges that student teaching poses on them. The literature adduced in the present paper points to a number of concerns that trainee teachers struggle with. First and foremost, they strongly complain about pupils’ misbehaviour and lack of motivation. Other stated problems include trainee teachers’ ineffective time and classroom management and feeling of anxiety that accompanies them throughout the whole period of practicum. In the present study we investigated the problems and worries of 108 student teachers majoring in English at the University of Silesia. The findings are congruous with the existing research in that pre-service teachers mostly struggle with pupils’ misbehaviour, time management, stress and feeling of anxiety. This emotional strain is caused by a number of factors: lack of confidence in one’s teaching skills, inability to introduce order and discipline, demotivated learners, being observed by a supervising teacher and conducting their first lesson.
Keywords: teacher education; student teaching; classroom management